Non-parental Adults and Sexual Health Behaviors Among Young Minority Men: A Qualitative Examination - Sterrett-Hong, Emma M.; DeBow, Joseph; Caton, Erica; Harris, Matthew; Brewer, Russell; Roberts, Erin; Marchal, Madeline; Tauzer, Marjorie; Arnold, Emily A. (Frontiers in Psychology, 2021)
Young ethnic/racial and sexual minority men (YESMM) exhibit disproportionately high rates of HIV compared to other groups, partly due to relatively higher rates of exposure to a host of socio-structural risk factors (e.g., unstable housing, under-employment). However, an under-studied interpersonal resource exists for many YESMM, non-parental adults (NPAs, i.e., adults who act as role models and provide social support), who may be able to influence contextual (e.g., unemployment) and individual (e.g., reduced health expectations) factors underlying HIV disparities. Aims. This study sought to examine the role of NPAs in factors that affect HIV-related health behaviors, and in supporting those health behaviors directly, among YESMM. A total of n = 20 participants, n = 10 YESMM and n = 10 NPAs, were interviewed using semi-structured guides to examine NPA involvement in the lives of YESMM from both sides of the relationship. The research team used a framework analysis approach to iteratively identify and define meaningful codes and sub-codes. Both YESMM and NPAs described NPAs helping YESMM through role-modeling and social support in a variety of areas found to affect HIV-related behaviors, such as housing instability, psychological distress, and future orientation, as well as in specific behaviors, such as HIV testing and medication adherence. Given the multiple socio-structural obstacles facing YESMM, and their multi-faceted relationships with NPAs, NPAs may be a promising resource for helping to address these impediments to health. Partnering more intentionally with NPAs is a potentially promising strategy to help reduce HIV-related disparities affecting YESMM that is worthy of additional empirical attention.